(untitled) (Research, Society and Development, 2022)
The insertion of psychology in the sports context consists of conquering its space and developing its practices as a team, so that its activities are carried out with success, promoting the well-being and results of athletes in training, as it has the role of in the reduction, harm and damage suffered by athletes. The general aspect of this article is the influence of Sport Psychology on the physical and mental investigation of the objective athlete. While the specific goals are the main mental illnesses that athletes can present; In addition to the importance of psychology in sport, in addition to identifying the factors that contribute to the mental and physical development of athletes. To carry out the same, they were published as sources published in scientific journals, using the National Library of Medicine (PUBMED), VHL (Virtual Health Library) databases, such as Lilacs (Latin American and Caribbean Literature on Health Sciences). ) ) and SciELO (Scientific Electronic Library Online), considering the keywords: psychology; sport and mental health. After analyzing the results, regarding the choice, considered as meeting a thematic study, published in full, with full texts available, being scientific articles or theses, in the languages: Portuguese, English and Spanish published between 2018 and 2022 We found a total of 18 articles in the scientific bases: Latin American and Caribbean Literature on Health Sciences (LILACS), National Library of Medicine (PUBMED), Virtual Health Library – (BVS), Scientific Electronic Library Online (SCIELO) ). In this review, we observed that the majority of researchers who approach this topic are important and show how their articles and the influence that affect athletes in a process of professional research are significantly during the process of psychological research.